Hak Isteri terhadap Harta Bersama dalam Perkawinan yang Putus Karena Kematian - I Gede Sukadana; I Nyoman Putu Budiartha; Diah Cayatri Sudibya (Jurnal Konstruksi Hukum, 2021)
Inheritance law is very closely related to the scope of human life, because every huma n being drill definiiely experience a legal event called death related to the problem of how to manage and continue rights and obligations ofa person who dies. This siudy aims to identify a wife's rights io joint property in a marriage that has been broken up due to death. The be of research used is a normative legal research method with a siaiuiory approach. Technique of collecting legal serials uses Documeiiiaiion Studies and Literature Studies. Results of windy show that the wife's right to joint property in a marriage that is broken up due to death, namely the wife has a half right to propert y because the property is obtained from results obtained from cooperation carried out by wife and husband who are already bound in marriage from the beginning of marriage to end. my husband has passed array. The legal remedy that can be taken by the wife is litigation, which is the seiilement of disputes in court and now-litigation, namely the senlement of dispWee outside the conn.